Pengembangan Jobsheet dan Trainer Kit PLC Pada Mata Pelajaran Sistem Kontrol Terprogram - Muhammad Adhitya Ramadhan; Syaiful Islami (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2023)
This study aims to develop jobsheets and trainers in portable form on the subject of Programmatic Control System, and find out how validity, practicality and effectiveness. This jobsheet and trainer are designed to be able to provide understanding of students who do not understand the entire PLC system from maintenance to programming. This research uses the IDI (Instructional Development Institute) development method, as for the IDI development procedures, namely define, develop, and evaluate. The data type is primary data where data is provided by experts, lecturers and students. Data is analyzed using Descriptive data analysis techniques, namely by describing the validity, practicality and effectiveness of the learning model developed. The results obtained from research and development are as follows: (1) Omron CPM1A PLC Jobsheet and Trainer Kit have been validated with three validators whose results are valid or with an average category of the three to 88% (2) The results of practicality testing have been obtained that jobsheets and trainers are categorized as very practical (95%) according to teacher assessment and practical (87%) according to student assessment (3) Meanwhile, in terms of effectiveness that Jobsheet and Trainer Kit PLC Omron CPM1A can be categorized as effective because the learning outcomes obtained using jobsheets and trainers are able to increase student learning completeness by more than 30% or from the average student score of 54.2 to 85.0.